RASIO-RASIO KEUANGAN YANG BERPENGARUH TERHADAP NON PERFORMING LOAN (NPL) (Studi Bank Umum Konvensional Periode 2016-2018 di BEI) - Shandy Marsono; Irwan Christanto Edy (Universitas Boyolali, 2021)
This study aims to determine financial ratios which include Return On Assets (ROA), Loan To Deposit Ratio (LDR), Operational Costs per Operating Income (BOPO), Net Interest Margin (NIM) and Capital Adequacy Ratio (CAR) against Non Performing Loans (NPL) at Conventional Commercial Banks that are Go Public which are listed on the Indonesia Stock Exchange in 2016-2018. This research is a quantitative descriptive study. The type of data used is secondary data obtained from www.bi.go.id and www.Idx.co.id. in the form of bank annual financial statements used as a sample with a time period of 3 years. While the sample of this study used purposive sampling method with certain criteria in order to obtain a sample of 14 banks. Based on the analysis method used, namely multiple linear regression which has passed the classical assumption test and hypothesis testing, the result is that partially Return on Assets (ROA) has a negative effect. significant, Loan To Deposit Ratio (LDR), Operational Costs per Operating Income (BOPO), and Capital Adequacy Ratio (CAR) have a negative and insignificant effect and Net Interest Margin (NIM) has a positive and insignificant effect on Non-Performing Loans (NPL). From the results of the analysis, the coefficient of determination is 0.240 or 24%. This means that the variables ROA, LDR, OEOI, NIM and CAR affect the NPL variable by 24%, while the rest is influenced by other variables outside of this study